Penerapan Project-Based Learning melalui Pembuatan Public Service Announcement (PSA) untuk Meningkatkan Hasil Belajar Sosiologi: Implementation of Project-Based Learning through the Creation of Public Service Announcements (PSAs) to Improve Sociology Learning Outcomes - Ni Nyoman Putri Nursanti; Nismawati Nismawati; Raudatul Jannah; Ulfa Della Nova Tilova (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Sociology learning plays a strategic role in equipping students to understand and analyze social phenomena critically. However, school learning practices are often dominated by conventional teacher-centered approaches, resulting in suboptimal student participation and learning outcomes. This study aims to describe improvements in sociology learning outcomes through the application of the Project-Based Learning (PjBL) model with Public Service Announcement (PSA) creation activities. The study used the Classroom Action Research (CAR) design model by Kemmis and McTaggart, which was implemented in two cycles: planning, implementation, observation, and reflection. The research subjects were 36 students from class XI IPS 3 SMAN 10 Jakarta, selected purposively because they had low average cognitive learning outcomes. Data collection techniques included observation of learning implementation, student attitude questionnaires, cognitive learning outcome tests, and documentation. Data analysis was conducted descriptively, qualitatively, and quantitatively. The results showed that applying PjBL through PSA creation improved the quality of the process and student learning outcomes. Learning implementation increased from an average of 73% in cycle I to 89% in cycle II. Student attitudes during learning also increased from 51% (less good) to 70% (good). In addition, cognitive learning outcomes increased from an average of 67 in the pre-cycle to 81 in cycle II, thus exceeding the Minimum Completion Criteria (KKM) of 75. These findings indicate that PjBL, through the creation of PSA, is an effective and contextually relevant learning strategy to improve sociology learning outcomes and encourage active student involvement in the learning process.